Dynamic Effects of CYP2D6 Genetic Variants in a Set of Poor Metaboliser Patients with Infiltrating Ductal Cancer Under Treatment with Tamoxifen (2019)
Breast cancer is a group of multigenic diseases. It is the most common cancer diagnosed among women worldwide and is often treated with tamoxifen. Tamoxifen is catalysed by cytochrome P450 2D6 (CYP2D6), and inter-individual variations in the enzyme due to single nucleotide polymorphisms (SNPs) could alter enzyme activity. We evaluated SNPs in patients from Colombia in South America who were receiving tamoxifen treatment for breast cancer. Allelic diversity in the CYP2D6 gene was found in the studied population, with two patients displaying the poor-metaboliser phenotype. Molecular dynamics and trajectory analyses were performed for CYP2D6 from these two patients, comparing it with the common allelic form (CYP2D6*1). Although we found no significant structural change in the protein, its dynamics differ significantly from those of CYP2D6*1, the effect of such differential dynamics resulting in an inefficient enzyme with serious implications for tamoxifen-treated patients, increasing the risk of disease relapse and ineffective treatment.